Penguatan Literasi dan Numerasi Melalui Pembelajaran Interaktif di SDN Sidorejo - Dwi Issadari Hastuti (Karsa Bhakti : Journal of Community Service, 2025)
This community service activity aims to improve the literacy and numeracy skills of elementary school students through an interactive and enjoyable learning approach. The program is carried out at SDN Sidorejo, involving lecturers, students, and school teachers as collaborative partners. The main issues faced are the low reading interest of students and difficulties in understanding basic arithmetic operations. The implementation method is conducted in three stages: planning, execution, and evaluation. In the planning stage, the team conducts a needs analysis and prepares learning media in the form of picture books, number cards, and educational games. The execution stage includes activities such as reading together, educational storytelling, and numeracy games like 'Quick Number Guess' and 'Math Puzzle' designed to foster students' enthusiasm for learning. Evaluation was conducted through pre-tests and post-tests to measure the effectiveness of the activities in improving students' abilities. The results showed an increase in the average literacy score from 63 to 84 and numeracy from 58 to 81, amounting to an improvement of 21% and 23%, respectively. In addition to having a positive impact on enhancing students' competencies, these activities also enriched teachers' insights in developing creative teaching methods that can be implemented sustainably. Thus, this community service activity successfully created an active, collaborative, and enjoyable learning environment and contributed to strengthening literacy and numeracy culture at the elementary school level.